Pengaruh Arus Kas Operasi, Tingkat Hutang, Ukuran Perusahaan, dan Volatilitas Penjualan Terhadap Persistensi Laba - Melin Fitryani; Dirvi Surya Abbas; Imam Hidayat; Kimsen (Pusat Riset dan Inovasi Nasional, 2022)
Users of financial statements need financial information from the company to analyze the financial performance of the company concerned. Financial ratios can be used as a tool to determine future profit growth. This study focuses on the usefulness of financial ratios to see future profit growth. The purpose of this study was to determine the growth of operating cash flows, debt levels, and company size on earnings persistence in basic and chemical industry subsidiary companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2021 period. The sampling technique used is the Pusposive Sampling technique. The total sample of this study was 14 samples. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. This research was processed using Eviews Version 9.0 software, using quantitative methods and using panel data analysis tools. The results showed that operating cash flow and Debt Asset Ratio (DAR) had an effect on earnings persistence. The sampling technique was 14 companies for the 2015-2021 research period. The tests used in this study were descriptive statistical analysis, panel data regression estimation, panel data regression model selection techniques, classical assumption tests, hypothesis testing, and multiple linear regression analysis.